Organic psychiatric disorders in the older persons - Chandrasekaran, PK; Srinivas, P (Journal of Institute of Medicine Nepal, 2008)
Background: A primary, retrospective study was done to determine the frequency and describe the patterns of presentation of delirium, dementia and mood disorder in the elderly. Methods: The sample was collected over 3 months and consisted of 10 patients above 60 years of age with features fitting those conditions, conventionally labeled at the time as Organic Brain Syndromes (OBS). Results: We found that OBS in hospitalized older people was common (29.41%) and the detection of these syndromes was poor, taking almost 5 days for a psychiatric referral to be made. Clinical presentations heterogeneously varied and the majority of cases were in a delirium (60%) due to various causes. Only low dosages of treatment were required to treat the symptoms, except in those who had a premorbid psychiatric disorder. Finally, symptom resolution was achieved (30%) only where the medical conditions causing the OBS were reversible, as is expected. Conclusion: This cost-effective study found that OBS in hospitalized older people was common, frequently diagnosed late and had a varied presentation. Key words: Delirium, Dementia, Depression, Pseudodementia, Post-stroke dementia The full text of this paper is available at Journal of Institute of Medicine website